In Search for Factors that Drive Hantavirus Epidemics - Heyman, Paul; Thoma, Bryan R.; Marié, Jean-Lou; Cochez, Christel; Essbauer, Sandra S. (Frontiers in Physiology, 2012)
In Europe, hantaviruses (Bunyaviridae) are small mammal-associated zoonotic and emerging pathogens that can cause hemorrhagic fever with renal syndrome (HFRS). Puumala virus, the main etiological agent carried by the bank vole Myodes glareolus is responsible for a mild form of HFRS while Dobrava virus induces less frequent but more severe cases of HFRS. Since 2000 in Europe, more than 3000 cases of HFRS have been recorded, in average, each year, which is nearly double compared to the previous decade. In addition to this upside long-term trend, significant oscillations occur. Epidemic years appear, usually every 2-4 years, with an increased incidence, generally in localised hot spots. Moreover, the virus has been identified in new areas in the recent years. A great number of surveys have been carried out in order to assess the prevalence of the infection in the reservoir host and to identify links with different biotic and abiotic factors. The factors that drive the infections are related to the density and diversity of bank vole populations, prevalence of infection in the reservoir host, viral excretion in the environment, survival of the virus outside its host, and human behaviour, which affect the main transmission virus route through inhalation of infected rodent excreta.. At the scale of a rodent population, the prevalence of the infection increases with the age of the individuals but also other parameters, such as sex and genetic variability, interfere. The contamination of the environment may be correlated to the number of newly infected rodents, which heavily excrete the virus. The interactions between these different parameters add to the complexity of the situation and explain the absence of reliable tools to predict epidemics. In this review, the factors that drive the epidemics of hantaviruses in Middle Europe are discussed through a panorama of the epidemiological situation in Belgium, France and Germany.